Experimental Evaluation of Modified T-Stub Connections for Seismic Applications - Prasetyo, Totok Andi; Antonius, Antonius; Sumirin, Sumirin (Pandawan, 2026)
This study aims to analyze the structural behavior of Modified T-Stub steel connections under cyclic loading, with the expectation that the results can be applied to steel construction in Indonesia, particularly for structures requiring high seismic performance. In this research, conventional 4ES and Double T-Connections were modified into Modified T-Stub configurations to improve their deformation capacity, strength, and energy dissipation performance. Experimental cyclic loading tests were conducted to evaluate the structural response of the modified connections, focusing on parameters such as strength, stiffness degradation, and drift capacity. Two test specimens were used, namely WF 450×200×9×14 and WF 500×200×10×16, which represent commonly used steel profiles in Indonesian construction practice. Numerical simulations were also performed to support and validate the experimental results. The test results indicate that both specimens exhibited stable hysteretic behavior and satisfactory performance under repeated cyclic loading. The numerical analysis showed that the connections were able to achieve drift ratios of up to 5% radian, while the experimental tests demonstrated drift capacities of approximately 4% radian without significant strength degradation or premature failure. These findings demonstrate that the Modified T-Stub connections meet the performance requirements for certified Special Moment Connections (SMC). This study provides valuable insights into the development of high-performance steel connection systems and contributes to enhancing the safety, efficiency, and structural quality of steel buildings in seismic regions of Indonesia.